2017
DOI: 10.14310/horm.2002.1718
|View full text |Cite
|
Sign up to set email alerts
|

Psychological vulnerability to stress in carriers of congenital adrenal hyperplasia due to 21-hydroxylase deficiency

Abstract: ObJeCTIVe: Carriers of congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency (21-OHD) demonstrate increased secretion of cortisol precursors following ACTH stimulation, suggestive of impaired cortisol production and compensatory increases in hypothalamic corticotropin-releasing hormone (CRH) secretion. both cortisol and CRH have behavioral effects, and hypothalamic CRH hypersecretion has been associated with chronic states of anxiety and depression. We performed an endocrinologic and psychologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…We therefore did not find a statistical difference between the parents of children with CAH and HT. Previous studies have suggested that carriers of CAH may have psychological vulnerability to stress ( 15 , 16 ). None of our parent participants were carriers of CAH.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore did not find a statistical difference between the parents of children with CAH and HT. Previous studies have suggested that carriers of CAH may have psychological vulnerability to stress ( 15 , 16 ). None of our parent participants were carriers of CAH.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, in congenital adrenal hyperplasia due to 21-hydroxylase deficiency, cortisol precursors are increasingly secreted with ACTH stimulation, indicating impaired cortisol production and compensating increased hypothalamic CRH secretion. In a study, carriers of 21-hydroxylase deficiency (i.e., parents of children with classical congenital adrenal hyperplasia) showed significantly higher state-anxiety scores than healthy subjects, and their mean 24 h urinary free cortisol excretion was significantly associated with psychoticism and paranoid ideation, thereby making them susceptible to anxiety disorders [ 54 ].…”
Section: Stress Depressive Symptoms T2d and Our Hypothesismentioning
confidence: 99%
“…As sexual maturation occurs during adolescence, this is a time during which clinicians can play a major role in supporting development of a healthy body image. Additionally, girls with CAH are at risk for developing an anxiety disorder (Kyritsi et al, 2017). An important aspect of social-emotional management for those with CAH is disclosure of sex development-related information to the child, in order to prepare for changes during puberty and ways in which they may appear differently from other children and adolescents.…”
Section: Social-emotional and Behavioralmentioning
confidence: 99%